Graphene‐Based Transparent Conductive Films: Material Systems, Preparation and Applications. Issue 1 (15th October 2018) - Ma, Yingjie; Zhi, Linjie
Abstract: The rising demands of optoelectronic devices, such as flexibility, stretchability, and energy efficiency, urgently require alternative transparent conductive films (TCFs) for indium tin oxide. Among all the candidates such as carbon nanomaterials, metal nanomaterials, conductive polymers, and other nanocomposites, graphene is highly promising because of its distinct properties, such as outstanding conductivity, impressive optical transparency, remarkable mechanical flexibility, and chemical/thermal stability. However, the practical application of graphene‐based TCFs (G‐TCFs) is still challenging due to the difficulty for preparing large‐area crystalline graphene with few defects for TCFs. Many efforts have been made to solve these problems, and several kinds of optoelectronic devices have been successfully fabricated with G‐TCFs. This review presents the recent development in this area made by the authors and others, including the material systems and synthetic strategies of G‐TCFs, as well as their applications as transparent electrodes in optoelectronic devices such as field effect transistors, organic light‐emitting diodes, organic solar cells, and other devices. The current major challenges in this area and the potential practical solutions are identified. Abstract : Graphene‐based transparent conductive films (TCFs) applied as transparent electrodes in optoelectronic devices are reviewed. Graphene is favorable to fabricate TCFs because of its distinct properties, including outstanding carrier mobility and conductivity, impressive optical transmittance, excellent mechanical flexibility, and chemical/thermal stability. Advantages and limitations of G‐TCFs are discussed together with future tendency of research.